1974
DOI: 10.1113/jphysiol.1974.sp010657
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin and the prostaglandin hypothesis of coronary blood flow regulation

Abstract: SUMMARY1. Recent experimental data support the view that prostaglandins might be involved in autoregulation of coronary blood flow. Since indomethacin blocks prostaglandin synthesis, the present study was performed to determine whether indomethacin also inhibits coronary vasodilatation induced by hypoxia.2. Coronary and systemic haemodynamic and metabolic effects of hypoxia (5 % and 8 % oxygen in nitrogen) were studied in intact, anaesthetized and vagotomized dogs before and after indomethacin. 3. 30 and 60 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…5 In our experiments the increase in the volume of coronary blood flow during hypoxia was also not substantially altered by the inhibition of PG synthesis. Afonso et al, 4 on the other hand, reported that IND administration slightly reduced the peak increase in flow following similar exposures to hypoxia. However, measurement of volumeflow is a better indicator of oxygen delivery to the tissue during hypoxia than measurement of peak flow.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…5 In our experiments the increase in the volume of coronary blood flow during hypoxia was also not substantially altered by the inhibition of PG synthesis. Afonso et al, 4 on the other hand, reported that IND administration slightly reduced the peak increase in flow following similar exposures to hypoxia. However, measurement of volumeflow is a better indicator of oxygen delivery to the tissue during hypoxia than measurement of peak flow.…”
Section: Discussionmentioning
confidence: 96%
“…It was reported recently that prostaglandins not only are released into the myocardial circulation during episodes of hypoxia, 4 anoxia, 5 and following coronary artery occlusion 6 -7 or administration of bradykinin, 8 but also that the ensuing increase in blood flow is attenuated in the presence of PG synthesis inhibitors. Other investigators, using similar experimental techniques, have found that the inhibitors had no significant effect on the vascular responses of coronary blood vessels.…”
mentioning
confidence: 99%
“…Other possible explanations might relate to inhibition of histamine release [24] , its role as an oxygen radical scavenger [25] , inhibition of calcium in smooth muscle cells [6] or modulation of the adrenergic neurotransmission to blood vessels [26] . In experimental studies on anaesthetized dogs by Afonso et al [9] , intra-coronary infusion of prostaglandins E 1 and E 2 were 5-10 times more effective in increasing coronary sinus blood flow than adenosine.…”
Section: Prostaglandins: Role In Modulation Of Systemic Flow Haemodynmentioning
confidence: 99%
“…Previous experimental data have suggested that prostaglandins play an important role in autoregulation of coronary artery blood flow [9] . Interference with this autoregulatory mechanism could alter coronary perfusion, which in turn could potentially affect myocardial function.…”
Section: Indomethacin and Coronary Blood Flowmentioning
confidence: 99%
“…The vasodilating ac tion of PGI2 may contribute to the signifi cant increase in coronary blood flow during reperfusion regardless of the temperature during ischemia under CP. Regarding the reactive hyperemia and PGI2, Alexander et al [14] and Afonso et al [15] reported that PGI2 might closely accompany the coronary flow rate. Adenosine has been shown to have a major role in reactive hyperemia following myocardial ischemia [16,17].…”
Section: Role O F Pgi2 Release During Reperfusionmentioning
confidence: 99%